Current strategies toward safer mu opioid receptor drugs for pain management - Ehrlich, Aliza T. (Expert Opin Ther Targets, 2019)
INTRODUCTION: Pain relief remains a major public health challenge. The most efficient available painkillers are opioids targeting the mu opioid receptor (MOR). MORs are expressed in the areas of the brain [including pain and respiratory centers] that are important for processing reward and aversion. Thus, MOR activation efficiently alleviates severe pain, but the concomitant reward and respiratory depressant effects pose a threat; patients taking opioids potentially develop opioid addiction and high risk for overdose. AREAS COVERED: Ongoing efforts to generate safer opioid analgesics are reviewed here. The design of biased compounds that trigger MOR induced G protein over β-arrestin signaling, peripheral opioids, drugs targeting MORs in heteromers and drugs enhancing endogenous opioid activity are discussed. EXPERT OPINION: There is evidence that throttling MOR signaling may lead to an era of opioids that are truly efficient painkillers with lower side effects and risk of overdose. However, few of the drugs derived from the advanced approaches outlined here, are getting approval by regulatory committees for use in clinical settings. Thus, there is an urgent need to (i) better clarify mechanisms underlying the hazardous physiological effects of MOR activation, and (ii) fully validate the safety of these new MOR-based therapies.